The Explosive Phases of the 1210–38 CE Reykjanes Fires, SW-Iceland: Physical Volcanology and Shallow Conduit Processes - Jacqueline Grech Licari 1997- (2022)
The 1210-11 CE Younger Stampar eruption at Reykjanes started the 1211-1238 CE Reykjanes Fires. The fires featured up to five discrete events: the 1210-11 CE eruption, three offshore eruptions in 1223, 1226-7 and 1231 CE, and a possible fourth in 1238 CE. The 1226-7 eruption is considered the source of the Medieval tephra, a well-known marker layer in SW Iceland. The first phase of the 1210-11 CE eruption, a Surtseyan phase just offshore of Reykjanes, forming the Vatnsfell tuff cone, was followed by the second Surtseyan phase 500 m offshore, forming the larger Karlsgígur tuff cone, and then by a subaerial activity forming the 4-km-long Stampar spatter cone row and lava flow field. The two tuff cones consist of alternations of pyroclastic surge and tephra fall units, intercalated with units from simultaneous deposition from surge and fall and have volumes of ∼0.006 km3 and ∼0.044 km3. The Medieval tephra is the only widespread tephra layer from the 1210-1238 Reykjanes Fires inferred to be present in soil profiles in SW-Iceland. This inference is challenged by identification of two consecutive tephra layers from the 1210-1238 Fires in sediment cores from Lake Hestvatn, 100 km E of Reykjanes. The 0.2-cm thick upper layer is from 1226 CE and the 0.4 cm-thick lower layer from 1211 CE. Hence, it possible that what has been hitherto identified as a single tephra layer (i.e., the Medieval tephra) represents two tephra layers. Namely, one sector with an E-SE dispersal axis hugging the southern coast of the Reykjanes Peninsula (RP); another with a dispersal axis extending over the northern part of the RP. New dispersal maps for each sector indicate tephra fall volumes for the 1226 CE (Medieval tephra) eruption of ∼0.09 km3 and ∼0.11 km3 for the Surtseyan phases of the 1210-11 CE Younger Stampar eruption. This implies a total volume of 0.16 km3 for each event. Whilst these inferences require verification via further studies, they highlight the importance of such studies because events similar to those of the 1211 or 1226 CE ...